Neutrophil ratio trajectory and the short-term outcome of perinatal hypoxic-ischemic encephalopathy - Li, Yunxia; Lang, Yujie; Deng, Ke; Zhou, Dongmei; Kang, Lili; Li, Xiaoying (Frontiers in Pediatrics, 2025)
BackgroundPerinatal hypoxic-ischemic Encephalopathy (HIE) is a disease of high mortality and morbidity. The neutrophil ratio (NR), a key indicator, is widely used in clinical practice. However, the relationship between dynamically changing NR and the short-term prognosis of HIE is unclear. We aimed to explore the dynamic changes and potential classifications of NR over time using trajectory analysis and to investigate its relationship with the short-term prognosis of HIE.MethodsWe performed a retrospective analysis of medical records from patients at Shandong University Affiliated Children's Hospital from 2014 to 2022. NR trajectories were modeled in 605 HIE infants using latent growth mixture modeling from 0 to 4 weeks. Then using logistic regression analyze the relationship between NR trajectories and the short-term outcome of HIE. Finally, restricted cubic spline regression model were used to assess the nonlinear relationship between baseline NR and the outcome.ResultsTwo distinct NR trajectories could be modeled, a descending (class 1) and a ascending group (class 2). The ascending group (class 2) was associated with the poor outcome (OR 5.72, 95% CI 2.97–10.87, P < 0.001; ORadj 4.78, 95% CI 2.42–9.28, P < 0.001). A significant nonlinear relationship between NR and the risk of poor outcomes (F = 13.16, P < 0.001), potentially exhibiting a U-shaped relationship.ConclusionThe ascending NR group was strongly associated with poorer short-term outcomes. And both low and high NRs at baseline were associated with increased risk of poorer short-term outcomes.